High-flow versus conventional nasal cannula oxygen supplementation therapy and risk of hypoxia in gastrointestinal endoscopies: a systematic review and meta-analysis. Issue 3 (4th March 2022) - Doulberis, Michael; Sampsonas, Fotios; Papaefthymiou, Apostolis; Karamouzos, Vasileios; Lagadinou, Maria; Karampitsakos, Theodoros; Stratakos, Grigorios; Kuntzen, Thomas; Tzouvelekis, Argyrios
ABSTRACT: Background: Gastrointestinal endoscopy (GIE) represents a mainstay diagnostic and therapeutic procedure in clinical practice. Hypoxemia constitutes a major complication for endoscopists. Emerging evidence supports the utilization of high-flow nasal cannula (HFNC) over conventional nasal cannula (CNC) for avoidance of hypoxemia. Our aim was to compare the hypoxemia risk in patients undergoing GIE with HFNC versus CNC oxygen supplementation recruited by randomized controlled trials (RCTs). Methods: We searched in medical databases PubMed, EMBASE and Cochrane to identify RCTs investigating the abovementioned association. Enrolled studies were evaluated for risk of bias and inserted into a random effects model for meta-analysis; subgroup analyses and publication bias were also assessed. Results: Out of 271 articles, five RCTs were eligible (patients n=2656, HFNC 1299 and CNC 1357). A statistically significant reduced relative risk (RR) of hypoxemia among HFNC patients was revealed (RR=0.18, CI95%: 0.05–0.61), whilst with high heterogeneity (I2:79.94%, p<0.01). Patients undergoing upper GIE with HFNC displayed a significantly lower hypoxemia risk (96%, p<0.001, I2:15.59%), even after exclusion of endoscopic retrograde cholangiopancreatography cases (RR:0.03, CI95%:0.01–0.21), albeit with higher heterogeneity (I2:41.82%).         Conclusion: Patients undergoing upper GIE with HFNC experience significantly less hypoxemia burden than CNC counterparts. Further research is warranted to target optimal safety during endoscopy. Abbreviations: ASA, American Society of Anesthesiologists; ASGE, American Society for Gastrointestinal Endoscopy; BMI, Body Mass Index; CI, confidence interval; CNC, conventional nasal cannula; ERCP, endoscopic retrograde cholangiopancreatography; FiO2, fraction of inspired O2 ; GI, gastrointestinal; GIE, gastrointestinal endoscopies; HFNC, High-Flow nasal cannula; ICU, intensive care unit; PEEP, positive end-expiratory pressure; PRISMA, Preferred Reporting Items for Systematic Reviews and Meta-Analysis; RCTs, randomized control trials; RR, relative risk (or risk ratio)